2018
DOI: 10.17352/2455-488x.000027
|View full text |Cite
|
Sign up to set email alerts
|

Optimal composition of plaster mortar reinforced with palm fibers

Abstract: The aim of this study is the use of local materials (plaster, sand dunes and date palm fi ber) for the region of southern Algeria. By expand areas of the use of these materials in the fi eld of construction. Despite the large ament of gypsum, its use is limited to some secondary operations like coatings and decorative elements. The sand dunes and palm fi ber, its use in the construction are very limited. In this study, the sand dunes and palm fi ber was added to plaster, to fi nd the mortar that has physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This treatment not only reinforced the mechanical properties of the fibers but also optimized their bonding strength with the fiber-matrix interface. The specific treatment conditions were established based on insights from recent studies [16,17]. In this process, initially cleaned fibers were immersed in a 1% NaOH solution at 100°C for a duration of one hour.…”
Section: Sample Preparationmentioning
confidence: 99%
“…This treatment not only reinforced the mechanical properties of the fibers but also optimized their bonding strength with the fiber-matrix interface. The specific treatment conditions were established based on insights from recent studies [16,17]. In this process, initially cleaned fibers were immersed in a 1% NaOH solution at 100°C for a duration of one hour.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Basha et al (2020) have indicated that raising the amount of RPA in self-compacting concrete can result in a reduction in its compressive strength, this is a consequence of the debonding between RPA and the mortar matrix. Moreover, RPA is more prone to absorbing water, which increases the porosity of the concrete (Rachedi, 2018), and this can lead to a decrease in the strength of the concrete. The same can be seen in Figure 8(a), which shows the inverse correlation between RPA and CS.…”
Section: The Effect Of Changing the Recycled Plastic Aggregates Conte...mentioning
confidence: 99%
“…This treatment improves the mechanical properties of the fibers and adjusts the adhesion strength of the fiber-matrix interface. The conditions for the treatment of fibers are based on the results of recent studies [15,16]. Firstly, the pre-prepared clean fibers were soaked in 1% concentration NaOH solution at 100°C for 1 h and then washed with water to remove the excess of NaOH sticking to the surface of the fibers, after that it bleached with sodium chloride, finally the fibers were washed again thoroughly with water and dried in the room temperature for 24 h before use.…”
Section: Pre-treatment and Preparation Of Fibersmentioning
confidence: 99%